2021
DOI: 10.1029/2020jc016708
|View full text |Cite
|
Sign up to set email alerts
|

A Global, Multiproduct Analysis of Coastal Marine Heatwaves: Distribution, Characteristics, and Long‐Term Trends

Abstract: In the context of global warming, extreme events in the ocean have recently received much attention among the scientific community. In the oceans, marine heatwaves (MHWs) have recently gained notoriety among the scientific community primarily due to their catastrophic impact on ecological communities (Collins et al., 2019; Garrabou et al., 2009; Wernberg et al., 2012) and fisheries productivity (Pearce et al., 2011) around the globe. MHWs are discrete events characterized by strong positive temperature anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 50 publications
2
65
2
Order By: Relevance
“…MHW trends were consistent with increased air temperatures, increased moisture and decreased winds, suggesting a strong coupling of coastal ocean and land during extreme heat events. Marin et al (2021) provided a global assessment of coastal MHWs by selecting all coastal pixels in multiple global satellite Sea Surface Temperature (SST) datasets. Their study showed that similarly to the global ocean, coastal MHW metrics had been largely increasing during the past decades, except for MHW intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MHW trends were consistent with increased air temperatures, increased moisture and decreased winds, suggesting a strong coupling of coastal ocean and land during extreme heat events. Marin et al (2021) provided a global assessment of coastal MHWs by selecting all coastal pixels in multiple global satellite Sea Surface Temperature (SST) datasets. Their study showed that similarly to the global ocean, coastal MHW metrics had been largely increasing during the past decades, except for MHW intensity.…”
mentioning
confidence: 99%
“…This approach is identical to that used in IPCC for the assessment of climate change trends and in the use of CMIP simulations (Bindoff et al, 2014). MHW trends are considered for a variety of metrics as their long-term changes are not uniform (Marin et al, 2021). In addition, we use outputs from two global ocean circulation models to evaluate these models' ability to capture cross-shore gradients of SST and MHW changes.…”
mentioning
confidence: 99%
“…Oliver et al 30 showed that the global trend to an increase in MHWs frequency and intensity was driven by the mean SST and not the variance almost everywhere except in the highly variable western boundary currents. Marin et al 32 however, focusing only on the very coastal region, showed that in the PCUS the general trend for a decrease in duration and intensity of MHWs was mostly driven by internal variability of the SST. We show here that, by removing the four years of the 38-year time series that correspond to the strongest EN conditions, the tendency for increased occurrence of MHWs shorter than 100 days in the PCUS might be the result of a higher SST variability.…”
Section: Resultsmentioning
confidence: 97%
“…Given the relatively small differences between different observational products, it is expected that most would result in very similar MHW metrics. An analysis of coastal MHWs around the planet indicates that the largest differences occur in mean MHW intensities, with much smaller differences in all other metrics (Marin et al 2021). Around Australia, most MHW metrics (aside from mean MHW intensities) are in agreement across products (Marin et al 2021).…”
Section: Methodsmentioning
confidence: 98%
“…Marine heatwaves (MHWs) have been increasing in their frequency, intensity, and duration across most of the world's oceans (Oliver et al 2018a;Laufkötter et al 2020) and coastal regions (Marin et al 2021) over the past century. These changes are largely due to anthropogenically-forced increases in air and ocean temperatures (Oliver et al 2018a;Oliver 2019), with further increases expected under continued global warming (Frölicher et al 2018;Oliver et al 2019).…”
Section: Introductionmentioning
confidence: 99%